Implementasi Good Governance (Studi: Kantor Dinas Kependudukan Pencatatan Sipil Kota Samarinda) - Josua Orlando; Jamiah Jamiah (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2022)
This study aims to provide additional knowledge about how to implement good governance which has become part of the governance of the implementation of the Indonesian state in general and specifically in the Population Office of Civil Registration of Samarinda City. The implementation of the state on the basis of Good governance has been mandated in article 3 of the Law of the Republic of Indonesia concerning the Implementation of a Clean and Free State from Corruption, Collusion, and Nepotism. The Law is also the basis for every institution / agency both from the central to the regional level in carrying out their duties and responsibilities, while the good governance in question is stated in the form of principles, namely; the principle of legal certainty, the principle of orderly state administration, the principle of public interest, the principle of openness, the principle of proportionality, the principle of professionalism, the principle of accountability, the principle of efficiency, and the principle of effectiveness.Penelitian ini bertujuan untuk memberikan tambahan ilmu mengenai bagaimana implementasi good governance yang telah menjadi bagian dari tata kelola penyelenggaraan negara Indonesia secara umum dan secara khusus di Dinas Kependudukan Pencatatan Sipil Kota Samarinda. Penyelenggaraan negara dengan dasar Good governance telah diamanatkan dalam Undang-Undang Republik Indonesia Pasal 3 tentang Penyelenggaraan Negara yang Bersih dan Bebas Dari Korupsi, Kolusi, dan Nepotisme. Undang-Undang tersebut juga yang menjadi dasar oleh setiap lembaga/instansi baik dari pusat sampai ke tingkat daerah dalam menjalankan tugas dan tanggungjawabnya, adapun good governance yang dimaksud tertuang dalam bentuk asas-asas yaitu; asas kepastian hukum, asas tertib penyelenggara negara, asas kepentingan umum, asas keterbukaan, asas proporsionalitas, asas profesionalitas, asas akuntabilitas, asas efisiensi, dan asas efektivitas.